Identification of Asiaticoside from Centella erecta (Apiaceae) as Potential Apyrase Inhibitor by UF-UHPLC-MS and Its In Vivo Antischistosomal Activity - Lara Soares Aleixo de Carvalho; Vinícius Carius de Souza; Vinícius C. Rodrigues; Aline Correa Ribeiro; Jorge Willian Leandro Nascimento; Priscila V. S. Z. Capriles; Priscila de F. Pinto; Josué de Moraes; Ademar Alves da Silva Filho (MDPI AG, 2022)
Schistosomiasis, caused by parasites of the genus Schistosoma, is a neglected disease with high global prevalence, affecting more than 240 million people in several countries. Praziquantel (PZQ) is the only drug currently available for the treatment. S. mansoni NTPDases (known as SmNTPDases, ATP diphosphohydrolases or ecto-apyrases) are potential drug targets for the discovery of new antischistosomal drugs. In this study, we screen NTPDases inhibitors from Centella erecta (Apiaceae) using an ultrafiltration combined UHPLC-QTOF-MS method and potato apyrase, identifying asiaticoside as one of the apyrase-binding compounds. After isolation of asiaticoside from C. erecta extract, we assessed its in vivo antischistosomal activities against Schistosoma mansoni worms and its in vitro enzymatic apyrase inhibition. Also, molecular docking analysis of asiaticoside against potato apyrase, S. mansoni NTPDases 1 and 2 were performed. Asiaticoside showed a significant in vitro apyrase inhibition and molecular docking studies corroborate with its possible actions in potato apyrase and S. mansoni NTPDases. In mice harboring a patent S. mansoni infection, a single oral dose of asiaticoside (400 mg/kg. p.o.) showed significantly in vivo antischistosomal efficacy, markedly decreasing the total worm load and egg burden, giving support for further exploration of apyrase inhibitors as antischistosomal agents.